IMPLEMENTASI SYSTEM MONITORING LINK OPTICAL LINE TERMINAL ICONNET BERBASIS ZABBIX SECARA REAL TIME - Agung Nugraha; Siti Nur (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Internet services are widely provided by many internet network provider companies, one of which is Indonesia Comnets Plus (ICON+) which is an internet network provider with fiber optic infrastructure that has a service called Iconnet. Iconnet is a high speed prepaid internet service using the latest fiber optic technology that is reliable and stable for retail and residential areas. One of the problems that exist in the Iconnet internet network service is about the problems that exist in its network devices, one of which is the lack of supervision of the Oprical Line Terminal (OLT) so that it remains in good condition or there is no loss for internet network distribution where the device directly leads to the customer. In order to avoid these problems, this final report will design an OLT monitoring system in the Iconnet service, especially on the Zabbix-based link so that it can be monitored through notifications via Telegram or directly with Zabbix. It is hoped that the monitoring system that will be created will run smoothly according to the features that have been planned so that it can make it easier for workers at PT ICON+ to efficiently handle problematic OLT.